Enhancing Efficiency in Container Handling Operations: A Multivariate Analysis: Meningkatkan Efisiensi dalam Operasi Penanganan Peti Kemas: Analisis Multivariat - Dian Arisanti; Juli Prastyorini; Syahrul Fazizal Bachtiar (Academia Open, 2023)
This study aims to identify and comprehend the implications on efficiency of Human Resources (HR), loading and unloading equipment, systems and procedures, as well as the operational aspects of Container Yard (CY) in a maritime terminal. Employing the SPSS methodology, our analysis reveals significant and profound impacts of HR (X1) on efficiency, with a beta coefficient of 0.523 (52.3%), highlighting HR's substantial contribution. Similarly, the isolated variable of Loading and Unloading Equipment (X2) exhibits a significant influence on efficiency, with a beta coefficient of 0.557 (55.7%). Moreover, System and Procedure (X3) demonstrate a noteworthy impact, with a beta coefficient of 0.511 (51.1%). Lastly, Container Yard (X4) also plays a significant role in efficiency, with a beta coefficient of 0.501 (50.2%). In sum, the combined effects of HR (X1), Loading and Unloading Equipment (X2), System and Procedure (X3), and Container Yard (X4) have a substantial influence on efficiency (Y) within the context of container handling operations. Highlight: HR Impact: Human Resources (HR) significantly contribute to efficiency in maritime terminal operations, accounting for 52.3% of the overall impact. Equipment Matters: Loading and unloading equipment play a crucial role, with a substantial 55.7% influence on operational efficiency. Procedural Efficiency: Effective systems and procedures, with a 51.1% impact, are essential for optimizing container handling operations in the maritime industry. Keyword: Efficiency, Human Resources, Loading and Unloading Equipment, Systems and Procedures, Container Yard